Influence of the principle of minimum potential energy on the distribution of density and gravitational energy of the Earth for the reference model PREM - М.М. Фис; А.Л. Церклевич (Геофизический журнал, 2021)
From the point of view of modeling the internal structure of the Earth, its figure and evolution play an important role, which to one degree or another are associated with gravitational energy and the principle of its minimization. The realization of the minimum principle of potential for models of the distribution of the Earth’s density is the key in studies on the detection of inhomogeneous mass distribution. Achieving the minimum gravitational energy of the Earth is equivalent to the approximation of the internal structure to the hydrostatic state, and this condition is achieved due to variations in density. Therefore, for correct geophysical interpretation of gravimetric data, it is necessary to align the PREM (Preliminary Reference Earth Model) with harmonic coefficients of geopotential and minimum functional condition that determines gravitational energy, and only on this basis to estimate variations in density and tectonosphere. An algorithm for representing a piecewise continuous density distribution function in a spherical PREM model by Legendre polynomials is proposed in the paper to calculate the density, potential and energy distribution in an ellipsoidal planet using an additional condition — the minimum of gravitational energy. The use of such an algorithm made it possible to transform the spherically symmetric PREM model to a hydrostatically balanced state. It turned out that in the model obtained, the excess potential energy is concentrated in the inner and outer core of the Earth, and also insignificantly in the planet’s crust. The total energy E for the PREM reference model, which is subdivided into ellipsoidal layers, is 2.3364∙1024 erg, and in the modified PREM model after its correction for the hydrostatic component, it is 2.2828∙1024 erg. Estimation of density redistribution and identification of areas of their greatest change provide a mechanism for explaining the dynamic processes in the middle of the Earth.